ViMeLa Project: An innovative concept for teaching mechatronics using virtual reality - Goga Cvetkovski, Lidija Petkovska, Paolo Di Barba, Maria Evelina Mognaschi, Dorota Kamińska, Anna Firych-Nowacka, Slawomir Wiak, Mihail Digalovski, Maja Celeska, Najmeh Rezaei, Marcin Lefik, Grzegorz Zwoliński, Tomasz Sapiński, Toomas Tikk, Rain Eric Haamer, Gholamreza Anbarjafari (Wydawnictwo SIGMA-NOT, sp. z.o.o., 2019)
In this paper, we present joint European project ViMeLa, which is based on a blended-learning method using theory classes and virtual reality (VR) as experimentation tool. The idea to create Virtual Mechatronic Laboratory for learning and teaching students in Mechatronics, came from the University of Technology in Lodz, with participation of the Universities in Skopje, Pavia and Tartu. In the frame of the project, flexible solutions are developed. Three scenarios are part of the project, namely: design, construction and operating principles of electric motors; industrial automation solution for controlling the process of sorting packages in a warehouse; industrial and domestic waste sorting line with belt.
Keywords: Virtual reality, Sensors; Interactive Environment in VR; Mechatronics; Electric machines; Actuators